Investigation of experimental study of biomass performance of wood pellets, palm shells, and rice husk in vacuum pressure gasification system - Tri Setioputro, Novandri; Kosim, Muhtar; Iman Saputra, Dede (Journal of Earth Energy Engineering, 2023)
Biomass-based renewable energy research has gained extra momentum due to the energy crisis from fossil fuels and global warming. Vacuum suction gasification can create combustible power plant synthesis gas. In vacuum gasification, palm shell biomass and wood pellets have better performance than rice husks. Palm kernel shells and wood pellets can produce stable synthetic gas for 6.5 hours, and the indicator is a flare for 6.5 hours. Another indicator is that palm shells and wood pellets can maintain a sustainable high temperature in the reactor. Rice husk is not suitable for this type of gasification. It does not maintain the high temperature necessary for the gasification process to work properly. The mass of rice husk, which is lighter than other biomass, causes the risk husk to be unable to push it down to the bottom of the reactor so that it becomes empty. This massive event will cause the biomass and temperature in the reactor to drop suddenly. The value of heat loss in the reactor wall is quite large, more than 2000 watts, which may be a factor causing the performance of vacuum gasification to not be optimal. In this experiment, the addition of water to the reactor was tested to determine the performance behavior of the system. Palm shells respond well to this treatment. This results in a sustainably better syngas output. Wood pellets do not respond well because they are easily damaged by water. The rice husks failed to respond. The syngas produced by the reactor is burned and used to boil water. In this gasification system, palm shells and wood pellets have a heating value of 5.62 kW and 5.41 kW, respectively. The efficiencies of palm shell and wood pellets were 29.20 percent and 29.96 percent, respectively.